A Comprehensive Evaluation of Digital Economy Development Level in China Based on the TOPSIS Method - Chen, Yining (Transactions on Economics, Business and Management Research, 2024)
Exploring the measurement of the digital economy development level plays a crucial role in analyzing the disparities in digital economy development across China’s provinces, formulating differentiated policies, and promoting balanced national digital economy development. This study first constructs an evaluation system for digital economy development levels, comprising 14 tertiary indicators. The weights of each indicator were determined using the Analytic Hierarchy Process (AHP), revealing that the number of domain names, the number of Internet broadband access users, as well as fiber optic cable line length, are significant factors. Subsequently, the TOPSIS method was utilized to measure and compare the digital economy development levels of 31 provinces (autonomous regions and municipalities). The results indicate that coastal provinces such as Guangdong, Jiangsu, and Zhejiang have higher levels of digital economy development, while the development levels in the central and western regions are relatively lagging. The study proposes policy recommendations to narrow the inter-provincial digital economy development gap and promote balanced and sustainable digital economy development nationwide, including strengthening infrastructure construction, implementing differentiated policies, fostering regional coordinated development models, and optimizing the talent cultivation system.